A study of phosphorus sediment distribution at Putrajaya Wetland using geographic information system (GIS - ArcMap) modeling - Zahari N.M.; Gye S.K.; Zawawi M.H.; Chow M.F.; Mohamad D.; Haron S.H.; Nazmi I.; Hassan M.; Isa R.M.; Sapian A.Z.; Noordin N.; Rahaman N.A.; et al. (American Institute of Physics Inc., 2023)
This paper studies the sediment phosphorus distribution pattern at a man-made freshwater tropical wetland in Malaysia known as Putrajaya Wetland. Phosphorus in sedimentation were extracted in form dissolved phosphorus and measured using HACH Method 8048. Result shows as contour mapping to identify the phosphorous distribution. The total phosphorus content of the sediment samples taken throughout the sampling period ranges from 1.23 mg/kg dw to 8.43 mg/kg dw. At the Lower East arm, total phosphorus is the highest with up to 8.43 mg/kg dw at Lower East 2. The inorganic phosphorus is the dominant phosphorus species in the sediments at the Upper North arm. Wetland sediments at the rest of the water bodies at wetland arms are dominated by organic phosphorus. The sediment consist of inorganic phosphorus as an important role in internal cycling and dominated by organic phosphorus experience slow phosphorus recycling process by microbes and vegetation over the long term and can prevent internal loading of phosphorus to the overlying water. 2018 Author(s).